Mecistogaster linearis (Fabricius) (Odonata: Coenagrionidae): First Record from Mato Grosso do Sul State, Brazil - Rodrigues, Marciel Elio; Koroiva, Ricardo; Ragalzi-da-Silva, Eric; de Moura, Emanuelle Batista (EntomoBrasilis, 2016)
Commonly called “helicopter damselflies”, Mecistogaster species (Coenagrionidae) are recognized by their large body size in comparison with other Odonata species, ability to flap both anterior and posterior wings in opposite directions, and preference for dense forest. These species feed on spiders and require trunks or plants that can accumulate water, like bromeliads, for laying eggs. This relationship with phytotelm environments makes the Mecistogaster species sensitives to forest fragmentation and habitat changes. In Brazil, there are records of seven species, mainly in Amazon forest regions. Mecistogaster linearis (Fabricius) has a wide distribution reported in the Brazilian states of Acre, Amazonas, Roraima, Pará, Rondônia, Mato Grosso, Rio de Janeiro, and São Paulo. Herein, we report the first record of M. linearis in the state of Mato Grosso do Sul with specimens sampled from the municipality of Corumbá, in the Pantanal. Mecistogaster linearis (Fabricius) (Odonata: Coenagrionidae): Primeiro registro para o Estado de Mato Grosso do Sul, Brasil Resumo. Conhecidas como “libélulas helicóptero”, as espécies do gênero Mecistogaster (Coenagrionidae) são caracterizadas pelo grande tamanho quanto comparado as outras espécies de Odonata, pela habilidade de bater as duas asas anteriores e posteriores em sentidos opostos e preferência por habitats de interiores de matas. Estas se alimentam de aranhas e dependem principalmente de troncos de árvores ou plantas, como bromélias, capazes de acumular água para a postura dos ovos. A relação com ambientes de fitotelmatas faz com que as espécies deste gênero sejam sensíveis a fragmentação florestal e a alterações em seu habitat. No Brasil há registros de sete espécies, com ocorrências principalmente em regiões de floresta amazônica. Mecistogaster linearis (Fabricius) tem uma ampla distribuição, sendo reportada, até então no país, para os estados do Acre, Amazonas, Roraima, Pará, Rondônia, Mato Grosso, Rio de Janeiro e São Paulo. Nesta comunicação, reportamos o primeiro registro desta espécie para o estado de Mato Grosso do Sul, Brasil, coligida no município de Corumbá, região do Pantanal.